2013
DOI: 10.1155/2013/627046
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase Deficiency Reduces Acetaminophen-Induced Hepatotoxicity and Lethality

Abstract: 5-Lipoxygenase (5-LO) converts arachidonic acid into leukotrienes (LTs) and is involved in inflammation. At present, the participation of 5-LO in acetaminophen (APAP)-induced hepatotoxicity and liver damage has not been addressed. 5-LO deficient (5-LO−/−) mice and background wild type mice were challenged with APAP (0.3–6 g/kg) or saline. The lethality, liver damage, neutrophil and macrophage recruitment, LTB4, cytokine production, and oxidative stress were assessed. APAP induced a dose-dependent mortality, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…This is also an analgesic, antioxidant and anti-inflammatory pathway [23,24,49,50]. Nrf2 also induces GSH production [51], therefore, this result is in agreement with the quercetin prevention of GSH depletion.…”
Section: Discussionmentioning
confidence: 53%
“…This is also an analgesic, antioxidant and anti-inflammatory pathway [23,24,49,50]. Nrf2 also induces GSH production [51], therefore, this result is in agreement with the quercetin prevention of GSH depletion.…”
Section: Discussionmentioning
confidence: 53%
“…AST and ALT levels in the plasma are widely used to assess liver damage. 22 These data demonstrated that treatment with 1 for 7 days does not induce liver damage, while the positive control of indomethacin induced a significant increase of these enzymes. Nonsteroidal anti-inflammatory drugs that are nonselective inhibitors of COX-1 induce gastric lesions, observed as increased MPO activity in stomach tissue samples.…”
Section: Journal Of Natural Productsmentioning
confidence: 81%
“…Tissue neutrophil ( Figure 3C) and macrophage ( Figure 3D) recruitment was assessed in the mice paw skin tissue by determining the myeloperoxidase (MPO) and N-acetyl-β-D-glucosaminidase (NAG) activity, respectively. 22 No effect was observed with the doses of 3 and 10 …”
Section: Journal Of Natural Productsmentioning
confidence: 93%
“…The quantitation of O 2 •-production in tissue homogenates was performed using the NBT assay as described previously [36]. Skin samples were collected 3 h after the stimulus.…”
Section: Abts Assaymentioning
confidence: 99%
“…RT-qPCR was performed as previously described [36]. Skin samples were collected 3 h after stimulus, homogenized in trizol reagent, and total RNA was isolated according to manufacturer's directions.…”
Section: Reverse Transcription and Quantitative Polymerase Chain Reacmentioning
confidence: 99%